Pengaruh Waktu Pemanasan dan Konsentrasi Larutan Pemasak Terhadap Kualitas Pulp dari Eceng Gondok (Eichhornia Crassipes) - Rony Tulak; Lyse Bulo; Tjodi Harlim (Prodi Teknik Kimia, 2022)
Pulping process from water hyacinth (eichronia crassipes) is done by using soda proces, where pulping process starting with the preparation of raw materials, cooking process using NaOH solution, washing with water, filtering and drying then analyzed to determine the quality of the pulp. The dried pulp is bleached using chorine.The Variable concentration of NaOH cooking solution 7%, 9%, 11% and cooking time 90, 120, 150 minutes are the variable which used to determine its effect on the quality of the pulp produced. Meanwhile, the parameters tested to determine the pulp quality are yield (% yield), moisture content and physical strength of the pulp.On this research were obtained that the optimum concentration at 7% and cooking time at 90 minutes with % yield of 17,167% , moisture content 9,615%, tensile strength (Force) 25,47 N and voltage (σ) 2,461 MPa.